Perancangan Interior Revitalisasi Gedung Kesenian Societeit de Harmonie di Makassar - Grace Mulyono, Edward Tanriady Muhammad Solahuddin (Intra, 2013)
Building in Makassar Societeit de Harmonie is a Dutch heritage building that was once used for art events. Current conditions because of the passage of time, the building was not maintained and can no longer be used in accordance with its function.The design goals are: Interior design (Revitalization) Arts Societeit de Harmonie which can meet the needs of the community art activities Makassar, maintain the historical value of the Arts Societeit de Harmonie, can be a place or container of artists gathering, and so the building was still known as well as a historical heritage building one characteristic of Makassar. Traditional Art Deco concept of Makassar was taken because the art form of architectural building using art deco style, so that the harmony of the interior of the theater was designed art deco style with traditional decorative elements Makassar. Interior design theme is "Theater of Dreams", which is the desire and hope of the artists in the city of Makassar to have a place to express and develop their artwork. Interior designer (Revitalization) Arts Societeit de Harmonie is based on 4 aspects, that is: Atractive, Comfortable, Entertaining, and Commercial which applied to all space which includes chambers: Theater, Theater arena, Gallery, Lobby information, staff room, office , CafÃ©, and Toilet.